Collaborative caching architecture for continuous query in mobile database - Elfaki, Mohamed Ahmed; Ibrahim, Hamidah; Mamat, Ali; Othman, Mohamed (Science Publications, 2011)
Problem statement: Cooperative caching, which allows sharing and coordination of cached data among clients, is a potential technique to improve the data access performance and availability in mobile ad hoc networks. However, variable data sizes, frequent data updates, limited client resources, insufficient wireless bandwidth and client’s mobility make cache management faces many challenges. Approach: In this study, we propose a Cluster Cache Collaborative (CCC) to reduce the average delay and increase the local cache hit ratio. Our architecture considers several factors that affect cache performance, namely: access probability, query status, distance between the requester and data source/cache, and data size. A collaborative cache management strategy, intra/inter cluster, is developed that employs Last Recently Used (LRU) and Time-To-Live (TTL) as the replacement data policy. Results: Our proposed architecture is being evaluated and compared to previous study’ architectures, and result shows that our architecture is different from other approaches by including query status model into a collaborative caching architecture to reduce the number of hopes between the requested node and the source node. Conclusion/Discussion: Due to the limitations of previous study’ architectures, this study attempts to enhance the performance of the continuous query (collaborative cache management) with respect to the local cache hit ratio and the average delay.